Draft genome sequence of myo-inositol utilizing Aeromonas dhakensis 1P11S3 isolated from striped catfish (Pangasianodon hypopthalmus) in a local fish farm in Malaysia - Sayuti, Mohamad Azzam; Md Yasin, Ina Salwany; Saad, Mohd Zamri; Annas, Salleh; Liles, Mark R.; Tingbi, Xu; Amal, Mohammad Noor Azmai; Yusof, Mohd Termizi (Elsevier, 2022)
A hypervirulent pathotype of A. hydrophila (vAh) is responsible for Motile Aeromonas Septicemia (MAS) and causes mass mortalities among farmed carp and catfish species in the USA and China. One unique phenotype for vAh among other A. hydrophila strains is the ability to utilize myo-inositol as a sole carbon source. While screening for Aeromonas isolates from diseased fish that can grow using myo-inositol as a sole carbon source, A. dhakensis 1P11S3 was isolated from the spleen of striped catfish (Pangasianodon hypopthalmus) displaying clinical MAS symptoms from a freshwater farm in Malaysia. Aeromonas dhakensis is also an important pathogen in aquaculture, and in this study, we report the draft genome sequence for A. dhakensis 1P11S3, that utilize myo-inositol as a sole carbon source.